2008
DOI: 10.2341/07-101
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage of All-ceramic Crowns Using Self-etching Resin Luting Agents

Abstract: SUMMARYSelf-etching adhesive systems are a new generation of materials that possess acidic methacrylates that can generate self-adhesion. There is limited data reported on the marginal leakage of ceramic restorations bonded with self-etching adhesive materials. This study assessed and compared the amount of microleakage of bonded ceramic crowns using three different types of self-etching adhesive systems with and without a die spacer.Eighteen human molars were prepared for allceramic IPS Empress crowns and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 19 publications
4
38
0
3
Order By: Relevance
“…Among the luted crowns, failure loads for severely damaged teeth were higher for the Panavia F2.0 group, as shown by ANOVA and the unpaired two sample t-test. This is in good agreement with studies investigating the bond strength between dentine and luting agents 34) , microleakage 35) , the load fatigue of compromised teeth after use of different luting cements 36) , and the fracture resistance of alumina copings 8) ; in all of these, behaviour of composite resin cements was superior to that of modified resin cements. The catastrophic test results for the crowns fixed with glass ionomer cement, i.e.…”
Section: Discussionsupporting
confidence: 77%
“…Among the luted crowns, failure loads for severely damaged teeth were higher for the Panavia F2.0 group, as shown by ANOVA and the unpaired two sample t-test. This is in good agreement with studies investigating the bond strength between dentine and luting agents 34) , microleakage 35) , the load fatigue of compromised teeth after use of different luting cements 36) , and the fracture resistance of alumina copings 8) ; in all of these, behaviour of composite resin cements was superior to that of modified resin cements. The catastrophic test results for the crowns fixed with glass ionomer cement, i.e.…”
Section: Discussionsupporting
confidence: 77%
“…Methylene blue is in common use for the assessment of microleakage, as gauged by the contemporary (2007)(2008) literature in adhesive dentistry and in the assessment of dentine permeability. [4][5][6][7][8] Use of immersion rather than vacuum methods is commonplace with methylene blue tracer dyes in such studies, and is in line with our work on adhesive interactions; we agree however that vacuum methods may be appropriate when considering the root canal situation, where diffusion alone would not give adequate penetration over time.…”
Section: Microleakage Of Composite Resin Restorations: Authors' Replysupporting
confidence: 69%
“…3 Dye leakage can be conducted under vacuum pressure, since the validity of dye leakage studies has been questioned because of the possible effect of entrapped air on the ingress of the dye solution. 4 Studies have reported that vacuum pressure decreases the volume of entrapped air and allows complete dye penetration. 5 Also, the authors in this study have not mentioned which type of curing light was used, since the type of curing light accounts for the degree of polymerization shrinkage of composite resin which in turn affects the microleakage.…”
Section: Microleakage Of Composite Resin Restorationsmentioning
confidence: 99%
“…[3][4][5][6] Conventional dentin bonding agents are based on smear layer removing or dissolving techniques. These adhesive systems need several steps of application and most of them are technique sensitive.…”
Section: Introductionmentioning
confidence: 99%